Energy Babble - Andy Boucher, Bill Gaver, Tobie Kerridge, Mike Michael, Liliana Ovalle, Matthew Plummer-Fernandez, and Alex Wilkie (Mattering Press, 2021)
This is the story of a set of computational devices called Energy Babbles. The product of a collaboration between designers and STS researchers, Energy Babbles are like automated talk radios obsessed with energy. Synthesised voices, punctuated by occasional jingles, recount energy policy announcements, remarks about energy conservation made on social media, information about current energy demand and production, and comments entered by other Babble users. Developed for members of UK community groups working to promote sustainable energy practices, the Energy Babbles were designed to reflect the complex situations they navigate, to provide information and encourage communication, and to help shed light on their engagements with energy policy and practice. This book tells the story of the Babbles from a mix of design and STS perspectives, suggesting how design may benefit from the perspectives of STS, and how STS may take an interventionist, design-led approach to the study of emerging technological issues.